Pengaruh Online Learning, Pressure, Opportunity, dan Rationalization Terhadap Prilaku Academic Fraud di Masa Pandemi Covid-19 (Studi Pada Mahasiswa Universitas Pendidikan Ganesha) - Komang Kristina Dewi; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2022)
This study aims to determine Online Learning, Pressure, Opportunity, and Rationalization of Academic Fraud Behavior During the Covid-19 Pandemic. This research is a type of quantitative research. The population and sample in this study were students of Ganesha University of Education. The method of determining the sample used in this research is purposive sampling technique, so that students who have taken business ethics courses are selected. This study used 400 respondents. The data used in this study are primary and secondary data, primary data collected through questionnaires to respondents. Then the data collected was tabulated and processed using SPSS. The results of this study state that online learning, pressure, opportunity, and ratioalization have a positive and significant effect on student academic fraud behavior during the Covid-19 pandemic. This is due to the influence of the student environment and the lack of supervision from educators. If the supervision of the teaching staff is low, then the chances of students will be greater in committing academic fraud.